The Effectiveness Of Three Dimentional Shapes Learning Media Android Based On Students Of SDN 43 Takkalala After Covid-19 Pandemic - Akramunnisa, Akramunnisa; Jumarniati, Jumarniati; Ekawati, Shindy (Universitas Wiralodra, 2023)
Students' learning motivation is greatly influenced by the Covid-19 pandemic. This can be seen in student motivation which has greatly decreased during the Covid-19 pandemic, this has had an impact on student learning outcomes. The achievement of effective learning can be seen from the means used by educators in conveying material, namely learning media. One suitable media to use is Android-based learning media. In this study, the aim was to provide an explanation and description of the effectiveness of using instructional media. The learning media that has been developed before is a mathematics learning media on Android-based three dimentional shapes. In this study, the type of research used was quantitative research using a one-shot-case-study design. The method used to provide an overview of effectiveness is the method of collecting data using learning achievement tests, questionnaires, and direct observation. The indicators of the effectiveness of learning mathematics that will be measured are 1) Teachers' Ability to Manage Learning, 2) Student Activities, 3) Completeness of Student Learning Outcomes, 4) Student Responses. Data obtained from 21 research subjects involved in this study were analyzed descriptively qualitatively. The results of the research and analysis of the data obtained are based on indicators of effectiveness, namely 1) The results of the analysis of the teacher's ability to manage learning in the classroom are in the good category with a percentage of 83%, 2) The results of the analysis of student activities are in the very good category with a percentage of 85%, 3) The results of the Analysis of Learning Outcomes are in the good category with a percentage of 86%, 4) The results of the Student Response Analysis are in the good category with a score of 4.1. Based on the results of the analysis of all aspects of effectiveness that meet the good category. The results of the analysis of the data obtained show and provide conclusions that the use of Android-based geometric learning media in mathematics lessons is effective to apply